1992
DOI: 10.1002/neu.480230409
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of sprouting in organ culture after axotomy of an identified molluscan neuron

Abstract: We examined a variety of factors that might modulate the initiation of neurite outgrowth in an attempt to identify means by which its initiation might be accelerated. We examined this initiation from an identified molluscan neuron, Helisoma trivolvis buccal neuron B5 after axotomy, and determined whether the site of injury, temperature, ion channel blockers, pH, the second messenger cAMP, and protein synthesis affect the initiation of neurite outgrowth. Neurite outgrowth was assayed from axotomized neurons by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 111 publications
1
4
0
Order By: Relevance
“…In other words, the cell retains its unipolar configuration. These findings support the hypothesis that the initiation of sprouting is regulated locally at or near the site of injury (Berdan and Easaw, 1992).…”
Section: Discussionsupporting
confidence: 74%
“…In other words, the cell retains its unipolar configuration. These findings support the hypothesis that the initiation of sprouting is regulated locally at or near the site of injury (Berdan and Easaw, 1992).…”
Section: Discussionsupporting
confidence: 74%
“…HVA calcium currents have been recorded from growth cones of Helix neurons (Marom and Dagan, 1987) and of neuron B5 of Helisoma (Haydon and Man-Son-Hing, 1988). The calcium channel blocker La 3+ stimulates neurite outgrowth in B5 (Berdan and Easaw, 1992;Williams and Cohen, 1995). Berdan et al (1993) reported that chronic (4-6 days) depolarization by high K + slightly increases neurite outgrowth, but strongly reduces the amplitude of both LVA and HVA currents recorded in the somata, suggesting that the expression of LVA and HVA channels is suppressed.…”
Section: Neurite Growthmentioning
confidence: 98%
“…They have been shown to contribute to different phases of action potential repolarization (Sakakibara et al, 2005). The perfusion of a cocktail of 20 mM TEA and 5 mM 4AP, concentrations that have been suggested to be effective to block both K channels in Helisoma and Lymnaea (Berdan and Easaw, 1992;Staras et al, 2002), caused a decrease in firing frequency by 34.5 ± 2.7% (n = 7, P < 0.05) combined with an increase in action potential amplitude by 21.5 ± 0.3% (n = 7, P < 0.05) (Fig. 5D).…”
Section: K Channels Mediate the Da-induced Hyperpolarizing Effectmentioning
confidence: 99%